EXPRESSION OF INTERJECTIONS IN ENGLISH AND UZBEK (Scientific journal of the Fergana State University, 2024)
We know that exclamations are among the first units that appeared in the development of humanity. This article analyzes the origin of exclamations in English and Uzbek languages. In particular, aspects such as the structure and syntactic function of exclamations in English and Uzbek languages ​​have been studied. Exclamatory words are divided into groups and explained with examples.